POWAGA RZECZY OSĄDZONEJ A DOCHODZENIE ODSETEK OD ZALEGŁYCH ODSETEK - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
RES IUDICATA and Pursuing Interests for Interests in Arrears Summary The aim of the article is to explain the doubts concerning the admissibility of pursuing interest for interest in arrears. This problem evokes doubts in the practice. The article presents the interpretation of art. 482 of the Civil Code, which includes the prohibition of anatocism. The exceptions thereto were also discussed. If the plaintiff, apart from the basic claim, pursues interests as an additional claim, the issued verdict creates the state of res iudicata also with regard to interests (art. 366 of the Code of Civil Procedure). In case of filing a state of claims for the interests for the interests in arrears, which is one of the exceptions from the rule of anatocism, the plaintiff counts the interests from the moment of filing the statement of claims regarding